The human imprint on the unique geological landscape of the Western Caucasus - Mikhailenko, Anna V.; Ruban, Dmitry A.; Zorina, Svetlana O.; Nikashin, Konstantin I.; Yashalova, Natalia N. (Geologos, 2020)
Human intervention in the geological environment is commonly thought to pose a threat to geoheritage. However, new information from the Western Caucasus where unique geological features are concentrated in Mountainous Adygeya, implies that man-made features in fact add value to geoheritage. Such features include a lengthy artificial niche in the Guama Gorge, accumulations of large artificial clasts along the road leading to the Lagonaki Highland and the Khadzhokh Quarry with the artificial Red Lake. These contribute to the regional uniqueness of geosites and can be classified as geomorphological, sedimentary, economical and hydro(geo)logical geoheritage types. Interestingly, these artificial features have natural analogues in the study area. Such integrity of local geological landscapes urgently require special interpretations for guided excursions and explanatory panels for correct comprehension of the origin of these unique features on the part of unprepared tourists. Generally, the human imprint on geological landscapes of Mountainous Adygeya is significant and occasionally positive, which makes the entire geodiversity hotspot of special, international interest and an object for further investigations.